Pro-rich Inflation in Europe: Implications for the Measurement of Inequality - Eren Güner; Alfons Weichenrieder (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper studies the distributional consequences of a systematic variation in expenditure shares and prices. By using European Union Household Budget Surveys and Harmonized Index of Consumer Prices data, we construct household-specific price indices and reveal the existence of a pro-rich inflation in Europe. Particularly, over the period 2001-15, the consumption bundles of the poorest deciles in 25 European countries have on average become 10.5 percentage points more expensive than those of the richest decile. We find that ignoring the differential inflation across the distribution underestimates the change in the Gini (based on consumption expenditure) by up to 0.03 points. Cross-country heterogeneity in this change is large enough to affect the ranking of the countries in inequality measures.
Keywords: D31; 330; Inequality; Gini; EU countries; income dependent inflation